2006
DOI: 10.1007/s00122-006-0327-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the HMW glutenin subunits from Aegilops searsii and identification of a novel variant HMW glutenin subunit

Abstract: High molecular weight (HMW) glutenin subunits are conserved seed storage proteins in wheat and related species. Here we describe a more detailed characterization of the HMW glutenin subunits from Aegilops searsii, which is diploid and contains the S(s) genome related to the S genome of Aegilops speltoides and the A, B and D genomes of hexaploid wheat. SDS-PAGE experiments revealed two subunits (one x and one y) for each of the nine Ae. searsii accessions analyzed, indicating that the HMW glutenin subunit gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…tauschii have been characterized (Wan et al 2005). Evidence from molecular analysis demonstrated that the HMW glutenin subunits from wheat and related species have highly conserved structures, consisting of a signal peptide (21 residues), an N-terminal domain (86-89 residues in x-type and 104 in y-type subunits), a C-terminal domain (42 residues), and a central repetitive domain (630-830 residues) that is mainly responsible for differences in molecular weight of the subunits Wan et al 2002Wan et al , 2005Yan et al 2004;Sun et al 2006;Zhang et al 2006). The HMW glutenin genes, therefore, could derive from a common ancestor.…”
mentioning
confidence: 99%
“…tauschii have been characterized (Wan et al 2005). Evidence from molecular analysis demonstrated that the HMW glutenin subunits from wheat and related species have highly conserved structures, consisting of a signal peptide (21 residues), an N-terminal domain (86-89 residues in x-type and 104 in y-type subunits), a C-terminal domain (42 residues), and a central repetitive domain (630-830 residues) that is mainly responsible for differences in molecular weight of the subunits Wan et al 2002Wan et al , 2005Yan et al 2004;Sun et al 2006;Zhang et al 2006). The HMW glutenin genes, therefore, could derive from a common ancestor.…”
mentioning
confidence: 99%
“…Previously, Anderson and Greene (1989) suggested the following modes may results in sequence alteration: (i) single base and single repeat; (ii) deletions or additions with a repeat; (iii) deletions or duplications of blocks of repeats, with possible unequal crossover and slip-mismatching. The unequal crossover was detected in Aegilops searsii accession IG49077, which results into the recombinant of Glu-1 loci (Sun et al 2006). Based on the result that the 68 residues in the repetitive domain of 1Dx2.3* t were identical to those of the y-type subunits, we suggest that unequal crossing over between the two Glu-1 loci on the sister chromatids of the homologous chromosomes during meiosis might have resulted into the formation of this novel hybrid ORF (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…For example, an extra cystenin was detected in the N-terminal part of the repetitive domain of 1Dx5 subunit and this subunit has been frequently associated with improved processing quality in wheat varieties . 1S s x490771 contains an extra cystenin residue located at the C-terminal part of its repetitive domain, which is novel compared to x-type subunits reported before (Sun et al 2006). Although the size of N-and C-terminal domains is highly conserved in either x-and y-type subunits, the repetitive domain size is usually variable.…”
Section: Introductionmentioning
confidence: 96%
“…For example, a 纬-gliadin/LMW-GS chimeric gene was identified in wheat (Nagy et al 2005). In addition, one HMW-GS y-/x-type chimeric gene was characterized from Aegilops searsii (Sun et al 2006). Novel chimeric genes (between LMW-i-and LMW-m-type LMW-GSs) were isolated from both Aegilops kotschyi and Aegilops juvenalis (Li et al 2008a).…”
Section: Discussionmentioning
confidence: 98%